VARIABILITAS SAHAM PADA PERIODE SEBELUM DAN SESUDAH PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN 17 APRIL 2019 - Arum Tri Widiastuti; Risal Rinofah; Mujino Mujino (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
This research is about the differences of abnormal return and trading volume activity in the period before and after the election of president and vice president on April 17, 2019.This research uses event study method to measure market reaction on politic event that is happening in Indonesia. The data that is used in this research is secondary data obtained from IDX (Indonesia Capital Market Director) .The data is in the form of daily closing price of share, IHSG, LQ-45, number of share traded and a number of share outstanding .The sample of the research is company share included in the composite stock price index (IHSG) and LQ-45 during the observation period, seven days before and seven days after the election of president and vice president on April 17,2019  in Indonesia Stock Exchange. Analysis of the data of the research uses normality test and a paired sample t-test. The result of the research indicate that 1. There is no significant differences between abnormality return in period before and after the election of president and vice president on April 17, 20192. There is no significant differences between trading volume activity in period before and after the election of president and vice president on April 17, 2019.Keywords : abnormal return, trading volume activity, the election of president and vice president.